Pengaruh Kompetensi, Pelatihan, dan Disiplin Kerja Terhadap Kinerja Pegawai Badan Penanggulangan Bencana Daerah (BPBD) Kabupaten Lampung Timur - Rahmahnurul Amina; Oktavianur Oktavianur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The Regional Government, as the administrator of government, plays a crucial role in implementing development for the benefit of its people. The performance of employees at the Regional Disaster Management Agency (BPBD) of East Lampung Regency is suboptimal, influenced by a lack of facilities and infrastructure to support disaster management and victim care, a lack of outreach, and a lack of competent human resources in the field of disaster management.The purpose of this study is to analyze the collective influence of Competency, Training, and Work Discipline on the Performance of Employees at the Regional Disaster Management Agency (BPBD) of East Lampung Regency. This research is quantitative with a descriptive correlational approach. The population in this study was all 166 employees of the East Lampung Regency Regional Disaster Management Agency (BPRD) using proportional random sampling. Data analysis used multiple linear regression analysis.The results showed that competence had a positive effect on employee performance. Training had a positive effect on performance. Work discipline had a positive effect on employee performance at the East Lampung Regency Regional Disaster Management Agency. Competence, training, and work discipline simultaneously had a positive effect on employee performance at the East Lampung Regency Regional Disaster Management Agency.